Quality of life and functional outcomes after organ-preserving for oral and oropharyngeal squamous cell carcinoma - Ahmed, Wael Mohamed; Abrar Bhat , Mohammad; Abdelkader Elmenshawi, Mohamed; Hamdi, Osama Ahmed; Ali El Sead Ghiat, Alaa Abdelrhman; Alhazmi, Barrag (Journal of Neonatal Surgery, 2024)
Background: Combining organ preservation strategies with free-flap reconstructions is a leading approach in treating oral and oropharyngeal squamous cell carcinomas (SCCs). Objectives: The purpose of this study was to analyze the clinical characteristics, functional outcomes, and quality of life of patients undergoing organ-preserving surgery for oral and oropharyngeal squamous cell carcinoma. Methods: The study consisted of a single-institution retrospective cohort study with cross-sectional assessment for patients treated from January 2020 to December 2024. Functional outcomes were measured using the Voice Handicap Index-10 (VHI-10); speech intelligibility grading; dysphagia and other clinical severity measures, such as the Dewar's Scale (DOSS); and endoscopic functional swallowing tests. The participants' overall quality of life (QoL)was measured using the EORTC QLQ-C30 and QLQ-H&N35 functional outcomes questionnaires (QoL). Results: A total of 72 participants were included. Most were male and younger than 70 years with minimal comorbidities. Good voice, speech, and swallowing function were exhibited by more than half. Speech with 61% of the participants and swallowing functioning normally in 57% was present. Overall quality of life was good, with a mean global QoL score of 72.4 ± 18.9. Functional domain scores were high, particularly in the high range for the physical and emotional-social domains. Dry mouth and sticky saliva, associated with and occurring after radiotherapy, were the most severe symptoms. Conclusion: Patients with stage I and II oral and oropharyngeal cancer who undergo organ conservation with free flap techniques SCC have a good quality of life and functional outcomes with minimal treatment sequelae.